2011
DOI: 10.1186/1687-4722-2011-426793
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label classification of music by emotion

Abstract: This work studies the task of automatic emotion detection in music. Music may evoke more than one different emotion at the same time. Single-label classification and regression cannot model this multiplicity. Therefore, this work focuses on multi-label classification approaches, where a piece of music may simultaneously belong to more than one class. Seven algorithms are experimentally compared for this task. Furthermore, the predictive power of several audio features is evaluated using a new multi-label featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
308
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(327 citation statements)
references
References 34 publications
0
308
0
10
Order By: Relevance
“…As such, this has been suggested heuristically in numerous works [10,11,13]. Here we have shown that this can be derived as an approximate maximizer of the composite likelihood of the model in Figure 2.…”
Section: Mim and Jmi Criteria Under Br Transformationmentioning
confidence: 85%
See 1 more Smart Citation
“…As such, this has been suggested heuristically in numerous works [10,11,13]. Here we have shown that this can be derived as an approximate maximizer of the composite likelihood of the model in Figure 2.…”
Section: Mim and Jmi Criteria Under Br Transformationmentioning
confidence: 85%
“…Trohidis et al [11] present a comparison between the J Y:full X:full and J Y:none X:full criteria, but using χ 2 -statistic instead of mutual information, while recently these criteria were re-introduced under the problem transformation approach [10]. Doquire & Verleysen [4] proposed J Y:none X:none .…”
Section: Connections With the Literaturementioning
confidence: 99%
“…We evaluate the performance of label compression and recovery, and multi-label prediction of CL on 21 datasets from different domains and of different scales, including Bibtex ), Corel5k (Duygulu et al 2002), Mediamill (Snoek et al 2006), IMDB (Read 2010), Enron (Tsoumakas 2010), Genbase (Diplaris et al 2005), Medical (Tsoumakas 2010), Emotions (Trohidis et al 2008), Scene (Boutell et al 2004), Slashdot (Read 2010) and 11 sub datasets included in Yahoo dataset (Ueda and Saito 2002). These datasets are collected from different practical problems such as text classification, image annotation, scene classification, music categorization, genomics and web page classification.…”
Section: Datasetsmentioning
confidence: 99%
“…Multi-label classification algorithms [5] address that category of problems where multiple output classes must be selected for each input instance. Examples of multi-label classification include text [6] and music categorization [7]. The commonly used evaluation metrics for multi-label classification problems are hamming-loss, precision and recall.…”
Section: Introductionmentioning
confidence: 99%